А. де Лазари, О. Рябов: Русские и поляки глазами друг друга. Иваново 2007 - Żakowska, Magdalena (Przegląd Rusycystyczny, 2008)
А. де Лазари, О. Рябов: Русские и поляки глазами друг друга. Иваново 2007